EFEKTIVITAS PUPUK ORGANIK CAIR LIMBAH KULIT SINGKONG BATANG PISANG DAN AZOLLA TERHADAP PERTUMBUHAN DAN HASIL PAKCOY - Jemian, Katarina Kresensia (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
Farmers’ dependence on chemical fertilizers has led to a decline in soil fertility and environmental pollution, while organic waste remains largely underutilized. This study aims to analyze the effectiveness of liquid organic fertilizer (LOF) application made from cassava peel, banana stem, and Azolla pinnata on the growth and yield of pakcoy (Brassica rapa L.). POC was prepared using 2 kg of cassava peel, 2 kg of banana stem, 2 kg of Azolla pinnata, 2 kg of brown sugar, 1 L of EM4, and 8 liters of water. The research design used was a Completely Randomized Design (CRD) with five concentration levels (0%, 5%, 10%, 15%, and 20%) and each concentration replicated six times. The results showed a significant (p <0.05) effect of POC treatment on pakcoy height leaf number, and fresh weight. The 10% concentration produced the best results, with a significant increase in all measured parameters. In conclusion, the application of POC derived from cassava peel, banana stems, and Azolla pinnata at a concentration of 10% effectively increases the growth and yield of pakcoy plants, and can be recommended as an environmentally friendly alternative fertilizer. Keywords: Pakcoy, liquid organic fertilizer (LOF), cassava peel, banana stem, Azolla pinnata, growth and yield.